A Rapid Procedure for the Simultaneous Determination of Eugenol, Linalool and Fatty Acid Composition in Basil Leaves - Lucia Lenti; Daniela Rigano; Sheridan L. Woo; Ancuta Nartea; Deborah Pacetti; Filippo Maggi; Dennis Fiorini (Foods, 2022)
Eugenol and linalool are often the most abundant volatile compounds found in basil (Ocimum basilicum L., Lamiaceae) leaves, and they are interesting for the aroma they provide and for their numerous beneficial bioactivities. Their determination is thus needed for several purposes. In the present study, to avoid the previous isolation of essential oil, the direct solvent extraction is proposed coupled with a transmethylation to convert acyl lipids into fatty acids methyl esters (FAMEs), thus assessing the possible simultaneous analysis of eugenol and linalool with FAMEs by gas chromatography coupled to flame ionization detector (GC-FID). The method has been validated and applied to ten basil leaves samples in which eugenol and linalool were found in mean concentrations of 2.80 ± 0.15 and 1.01 ± 0.04 g kg−1 (dry weight), respectively. FAMEs composition was dominated by linolenic acid (52.1–56.1%) followed by palmitic acid (19.3–22.4%) and linoleic acid (9.6–11.3%). The ratio of n6-polyunsaturated fatty acids (PUFAs)/n3-PUFAs was in the range of 0.17–0.20 in the investigated samples. The proposed method exploits a rapid procedure requiring 40 min, making use of a small amount of solvent and allowing the simultaneous determination of molecules contributing to assess the quality of this worldwide appreciated herb.